HEALTH TECHNOLOGY ASSESSMENT UNIT PROCESSES FOR THE VALIDATION OF AN INFORMATION TOOL TO INVOLVE PATIENTS IN THE SAFETY OF THEIR CARE. (10th July 2018) - Poder, Thomas G.; Carrier, Nathalie; Bédard, Suzanne K.
Abstract : Introduction: Patients and families play an important role in preventing adverse events. The quality council at our hospital produced a communication tool in considering the main causes of adverse events and requested the health technology assessment (HTA) unit to validate it. Objectives: Assess the validity of the content of a tablemat sticker as an information tool for hospitalized patients. Methods: A qualitative validation was first performed with individual interviews and focus groups to evaluate the understanding of the content. The tool was modified and as a second step, a survey was conducted on patients and their families from a surgical care unit to validate their understanding and relevance of the content. Results: From the survey, patients and families found the tablemat attractive and stimulating (97 percent). It encouraged them to communicate with staff about the safety of their care (84 percent). They understood well the objective (79 percent) and text (90 percent), but less for the pictograms (30 percent to 62 percent). The communication and recommendations to avoid falling were good and 99 percent were wearing the medical identification. However, it was not clear that these indicators represented the real concerns of the patients and healthcare staff because no user evaluation was done when developing the tool. Conclusions: The tool was well understood, but some improvements are needed considering that pictograms were not always well understood and so need careful consideration from patient perspective. The HTA unit recommended conducting an unbiased survey to assess the concerns of patients and professionals to identify the most relevant indicators.